Sebaceoma on the scalp simulating a malignant pigmented neoplasia - Bárbara Catojo Poggi; Daniel Fernandes Melo; Juliana Marques da Costa; Maria Auxiliadora Jeunon Sousa
Abstract The correct identification of pigmented nodular lesions of the scalp is often challenging. Despite the importance of clinical patterns and dermoscopy, important adjuvant tools that are usually helpful, their interpretation sometimes is not clear-cut. Here, the authors discuss a case of sebaceoma mimicking a malignant pigmented neoplasia, with conclusive histopathology.